Is Economics Responding to Critique? What do the UK 2015 QAA Subject Benchmarks Indicate? - Morgan, Jamie (Review of political economy, 2015)
The Quality Assurance Agency for Higher Education provides subject benchmarks which inform but do not determine the content of university and college academic programmes in the United Kingdom. These are revised every few years and have recently been completed in economics for the first time since the global financial crisis. Given the extensive criticism of mainstream economics since the crisis, one might anticipate the benchmark revisions to be extensive. However, this has not been the case. This article explores why this is so. The analysis may also be considered of broader significance because the conditions under which the review has occurred involve general processes that will be familiar, albeit with local variation, to heterodox economists elsewhere. In the conclusion, a more fundamental reconstruction of the benchmarks is provided. These will also be of interest as general orienting statements for a different kind of economics.